High glucose facilitated endothelial heparanase transfer to the cardiomyocyte modifies its cell death signature. Issue 3 (14th December 2016) - Wang, Fulong; Jia, Jocelyn; Lal, Nathaniel; Zhang, Dahai; Chiu, Amy Pei-Ling; Wan, Andrea; Vlodavsky, Israel; Hussein, Bahira; Rodrigues, Brian
Abstract : Aims: The secretion of enzymatically active heparanase (Hep A ) has been implicated as an essential metabolic adaptation in the heart following diabetes. However, the regulation and function of the enzymatically inactive heparanase (Hep L ) remain poorly understood. We hypothesized that in response to high glucose (HG) and secretion of Hep L from the endothelial cell (EC), Hep L uptake and function can protect the cardiomyocyte by modifying its cell death signature. Methods and results: HG promoted both Hep L and Hep A secretion from microvascular (rat heart micro vessel endothelial cells, RHMEC) and macrovascular (rat aortic endothelial cells, RAOEC) EC. However, only RAOEC were capable of Hep L reuptake. This occurred through a low-density lipoprotein receptor-related protein 1 (LRP1) dependent mechanism, as LRP1 inhibition using small interfering RNA (siRNA), receptor-associated protein, or an LRP1 neutralizing antibody significantly reduced uptake. In cardiomyocytes, which have a negligible amount of heparanase gene expression, LRP1 also participated in the uptake of Hep L . Exogenous addition of Hep L to rat cardiomyocytes produced a dramatically altered expression of apoptosis-related genes, and protection against HG and H2 O2 induced cell death. Cardiomyocytes from acutely diabetic rats demonstrated a robust increase in LRP1 expression and levels of heparanase, a pro-survival gene signature, and limited evidence of cell death, observations that were not apparent following chronic and progressive diabetes. Conclusion: Our results highlight EC-to-cardiomyocyte transfer of heparanase to modulate the cardiomyocyte cell death signature. This mechanism was observed in the acutely diabetic heart, and its interruption following chronic diabetes may contribute towards the development of diabetic cardiomyopathy.